Revisiting Black Theology of Liberation in South Africa: Through "new voices" of women black theologians - Xhinti, Sandisele L. (HTS teologiese studies, 2021)
Black Theology of Liberation (BTL) has done significant work for many decades in the struggle for the liberation of black people. Black Theology of Liberation is a theology which restores human dignity and identity for black humanity, and it needs to be acknowledged and celebrated. One of the most important contributions BTL made was the creation of new forms of ecclesiological knowledge, resulting from a critical look at the use of the Bible with Eurocentric perspectives, and the organisational structures of the church divided between black and white, leading to, amongst others, the dismantlement of black African knowledge, systems and their culture. From a black theological perspective, ecclesiology focused on restoration of the dignity of black persons by dismantling Eurocentric views about faith and ecclesiology that have continued to demonise black lives. Black theology, with its positive contribution, focused on racism and other constructs of oppression such as class, with very little and limited focus on sexism and patriarchy. This article will demonstrate how significant the contribution of BTL has been and also decry or denounce the fact that patriarchal violence and the liberation of women were not given equal attention.Contribution: The article contributes to theological discourse in South Africa (SA) today. It is written from the perspective of BTL and premised by the experience of oppressed black persons. In this article, it has been stated that black persons and their lived experiences are epistemologies in the quest for liberation of black humanity as a whole. The article will therefore bring forth BTL epistemologies that have been put in the periphery by western theology.